PENGARUH KELAS IBU HAMIL TERHADAP KECEMASAN MENGHADAPI PERSALINAN PADA IBU HAMIL BERESIKO - Ganda Agustina Hartati; Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Jurnal Endurance, 2021)
Risk factors for pregnancy cause anxiety in the mother which can interfere with the pregnancyprocess and even the delivery process. The existence of a Class program for pregnant women canincrease the knowledge and skills of mothers regarding pregnancy, childbirth, postpartum care andnewborn care, and physical activity during pregnancy is expected to reduce maternal anxiety indealing with childbirth. This study aims to determine the effect of class of pregnant women on reducing anxiety levels in pregnant women. Quantitative research design with non-equivalent prepost-test control group design with a sample size of 30 in the experimental group and 30 in the control group. The research was conducted in the Sipahutar Community Health Center. The resultsshowed that there was a significant effect of class treatment of pregnant women on the level ofmaternal anxiety in facing childbirth, with a mean value of 36.10 and a standard deviation of 9.397and p value = 0.00. The conclusion of the study was that participation in the class of pregnant womenhad an effect on reducing maternal anxiety in dealing with labor